Noninvasive and targeted delivery of therapeutics to the brain using focused ultrasound - Poon, Charissa (Neuropharmacology, 2016)
The range of therapeutic treatment options for central nervous system (CNS) diseases is greatly limited by the blood-brain barrier (BBB). While a variety of strategies to circumvent the blood-brain barrier for drug delivery have been investigated, little clinical success has been achieved. Focused ultrasound (FUS) is a unique approach whereby the transcranial application of acoustic energy to targeted brain areas causes a noninvasive, safe, transient, and targeted opening of the BBB, providing an avenue for the delivery of therapeutic agents from the systemic circulation into the brain. There is a great need for viable treatment strategies for CNS diseases, and we believe that the preclinical success of this technique should encourage a rapid movement towards clinical testing. In this review, we address the versatile applications of FUS-mediated BBB opening, the safety profile of the technique, and the physical and biological mechanisms that drive this process.